Banking Unions: Distorted Incentives and Efficient Bank Resolution - Marius A. Zoican; Lucyna A. Górnicka (Tinbergen Institute, 2013)
This paper studies the optimality of a banking union in a setting with cross-country liquidity spillovers and moral hazard. Generally, the banking union improves welfare by efficiently providing liquidity to banks, thus limiting spillovers from bank defaults across the member countries. At the same time, however, the banking union will resort to bank bailouts more often, distorting risk incentives of banks. For low bank liquidation costs, the net welfare effect of a banking union can be thus negative. For welfare enhancing banking unions, countries with net creditor banking systems always pay most of the joint bailout costs. In equilibrium, all countries are less willing to join a banking union which induces moral hazard.
Keywords: G15; G18; G21; G33; 330; banking; financial intermediation; risk shifting; banking union